Pembuatan Laporan Harian Ketidaklengkapan Pengisian Catatan Medis (KLPCM) Menggunakan Google Spreadsheet - Gunawan; Faradisa Andhika Putri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The degree to which medical records are filled out completely is one of the criteria for determining how well they are kept in hospitals. Keep an eye on the assembly section's work in these areas. The Hasta Husada Special Surgery Hospital uses a mixed approach that combines traditional methods with that of WhatsApp, resulting in less than ideal outcomes for the evaluation of medical record completeness. In order to fill in the gaps in the monitoring model for medical record completion, this community service aims to find a more efficient alternative. Our interaction with the medical records section yielded recommendations for the development of an application based on a Google Spreadsheet paradigm. By working together on a mutually agreed-upon Google spreadsheet, our team was successful in creating the medical record filling incomplete monitoring application (KLPCM). it was tried.